If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3 (3d-2)=4-d
We simplify the equation to the form, which is simple to understand
-3(3d-2)=4-d
Reorder the terms in parentheses
+(-9d+6)=4-d
Remove unnecessary parentheses
-9d+6=+4-d
We move all terms containing d to the left and all other terms to the right.
-9d+1d=+4-6
We simplify left and right side of the equation.
-8d=-2
We divide both sides of the equation by -8 to get d.
d=0.25
| 12+5x=2x-11 | | 2x+x^2=224 | | 25=-n/6+(-19) | | 6(a-7)+10=4(a-7) | | 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 | | 24.75+6x=31.2+3x | | 4-7m=1-6m | | 1.25a=1.222 | | -3=-7t | | 4(x+6)-4=6(x+3)-6 | | 6y-5=7y | | 4x-6=x+49 | | 1.25a=1.22 | | 2x^2+89=-4 | | 1.25a=1.22222 | | 66w-37-23w=49 | | 52c-14-35c=133 | | 0.065(x+2000)=0.07x+0.04(1000) | | 5-(a+3)=2a+6-3a | | 7p+6p= | | 10x+6y=97.5 | | x-4=2(2x-5) | | 10x+3=7x+4 | | 7n-n+12= | | 2x=3x+29 | | 8y-3=5y-8 | | 0.6x-0.4(40+x)=0.3(40) |